THE EFFECT OF LOCUS OF CONTROL, EMOTIONAL INTELLIGENCE, AND PROFESSIONAL SKEPTICISM OF INTERNAL AUDITORS ON AUDIT QUALITY WITH AUDITOR EXPERIENCE AS A MODERATING VARIABLE - Dede Rosmiati; Syaiful Rahman Soenaria; Anies Rahman Lastiati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze in more depth the influence of locus of control, emotional intelligence, and professional skepticism on audit quality using auditor experience as a moderating variable. The data used are the results of questionnaires from 70 auditors in the Internal Audit Unit (SPI) of State Universities with Legal Entities (PTNBH). Hypothesis testing techniques used multiple linear regression analysis and moderated regression analysis. The results of the study indicate that locus of control and emotional intelligence have a positive effect on audit quality, while professional skepticism has no significant effect on audit quality. The results of the moderated regression analysis indicate that auditor experience weakens the interaction of locus of control on audit quality and auditor experience does not moderate the relationship between emotional intelligence and professional skepticism on audit quality. The implications of this study indicate that locus of control and emotional intelligence must be possessed by auditors because they are one of the factors that can produce good audit quality. In addition, the Internal Audit Unit (SPI) must hold regular training to strengthen professional skepticism, because professional skepticism cannot be formed instantly but gradually.